Social security in current environmental and economic development in Vietnam - Trần Thị Kim Liên (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
In recent years, although the social security policy has been paid attention by the State, all resources have been devoted to supporting the disadvantaged in society to ensure their lives and access essential services. However, in reality, the implementation of social security policy in the current economic and environmental conditions of our country faces many challenges, so it is necessary to synchronously deploy many solutions, suitable to the current economic and environmental conditions. The paper mentions a number of issues: (i) Perspectives on social security; (ii) The relationship between social security and economy & environment; (iii) Opportunities and challenges of implementing social security in the current economic and environmental context in Vietnam; (iv) Solutions for synchronously implementing social security policies in the current economic and environmental conditions.